Preliminary Overview of the Economies of Latin America and the Caribbean 2021 - Economic Commission for Latin America; the Caribbean (United Nations, 2022)
This edition of Preliminary Overview of the Economies of Latin America and the Caribbean analyzes the economic and social dynamics at play last year, and explores the risks and policy challenges that the region will face in 2022 for driving a transformative recovery. More specifically, the document presents new Gross Domestic Product (GDP) estimates for the region and all of its countries in 2021, along with projections for 2022.